Assessment of model villages in farming perspective using Model Village Potential Index - BHATTACHARYYA, SANGEETA; PONNUSAMY, KUPPUSAMY (The Indian Journal of Agricultural Sciences, 2017)
Indian villages shelter more than two third of population and ensures the country’s food and nutritional security through its agricultural activities. Hence both government and non government agencies undertake number of interventions to develop the villages. But what is the after effect of such intervention on a village as a whole? It is well known that research institutes and Krishi Vigyan Kendras (KVKs) under the Indian Council of Agricultural Research system adopt villages to disseminate technologies and other research outputs and in a way try to develop model villages fit to be replicated by other villages. A study was conducted at ICAR-NDRI to assess such Model Villages, adopted by IARI and NDRI in Haryana and Ramakrishna Ashram KVK in West Bengal. The villages were assessed mainly from farming perspective as agriculture is the backbone of Indian villages. But along with farming; infrastructural, economic, social and environmental parameters were also assessed through Model Village Potential Index because all are interlinked. The village Gilechant in West Bengal surpassed the other selected villages in infrastructural score (63/85), farming score (68/86) and environmental score (4/7). Except Budhakhera in Haryana, other villages had same economic scores (23/28). Budhakhera and Gilechant had equal social scores (21/29). The scores on all five indicators cumulatively yielded the Model Village Potential Index value 68.14 for Budhakhera, 71.83 for Kalvehri, 71.36 for Badarpur Saeed and 76.53 (highest) for Gilechant indicating the successful efforts of Ram Krishna Ashram KVK, West Bengal in developing this village into a Model Village.